Project Management Professional Lab Manual - Phillips, Joseph (New Delhi Tata McGraw Hill Education Private Limited, 2010)
An all-new PMP lab manual featuring hands-on practical labs to help certification candidates prepare for the most difficult topics on the PMP exam
Include Index
Keywords: Project management--Examinations -- Information technology--Management -- Project management -- Information technology projects